On the dilated facets of a Poisson-Voronoi tessellation - Redenbach, Claudia (Image analysis and stereology, 2011)
In this paper, the parallel set ksiR of the facets ((d-1)-faces) of a stationary Poisson-Voronoi tessellation in R2 and R3 is investigated. An analytical formula for the spherical contact distribution function of the tessellation allows for the derivation of formulae for the volume density and the specific surface area of ksiR. The densities of the remaining intrinsic volumes are studied by simulation. The results are used for fitting a dilated Poisson-Voronoi tessellation to the microstructure of a closed-cell foam.
Keywords: Aluminijev oksid; Polymers; Aluminum Oxide; Poissonova distribucija; Materiali, testiranje; Materials Testing; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; Poisson Distribution; Polimeri; obdelava slik; stohastična geometrija; Poisson-Voronoijev model